2017
DOI: 10.1093/cercor/bhx037
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Grasping Movements from the Parieto-Frontal Reaching Circuit in the Nonhuman Primate

Abstract: Prehension movements typically include a reaching phase, guiding the hand toward the object, and a grip phase, shaping the hand around it. The dominant view posits that these components rely upon largely independent parieto-frontal circuits: a dorso-medial circuit involved in reaching and a dorso-lateral circuit involved in grasping. However, mounting evidence suggests a more complex arrangement, with dorso-medial areas contributing to both reaching and grasping. To investigate the role of the dorso-medial rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
41
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 118 publications
12
41
1
Order By: Relevance
“…Interestingly, a very recent study using magneto-encephalography (MEG) in humans has demonstrated that both the dorsolateral (putative grasping) and the dorsomedial (putative reaching) stream play a critical role in planning of non-visually guided reaching vs. grasping actions 72 . Once again, this notion corroborates the hypothesis that grasping information is coded within both pathways, in line with multiple recent evidence collected both in human 40 , 54 , 73 75 and monkey studies 4 , 19 , 42 , 76 , 77 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Interestingly, a very recent study using magneto-encephalography (MEG) in humans has demonstrated that both the dorsolateral (putative grasping) and the dorsomedial (putative reaching) stream play a critical role in planning of non-visually guided reaching vs. grasping actions 72 . Once again, this notion corroborates the hypothesis that grasping information is coded within both pathways, in line with multiple recent evidence collected both in human 40 , 54 , 73 75 and monkey studies 4 , 19 , 42 , 76 , 77 .…”
Section: Discussionsupporting
confidence: 89%
“…While some neurons showed a strong preference for reach-to-grasp movements, others showed a strong preference for reach-to-press movements. In line with increasing evidence for a significant role of area V6A and, more generally, of the dorsomedial visual pathway in the encoding of grasping movements 4 , 19 , 41 , 42 , the majority of cells with significant task-related activity showed a preference for the Reach-to-Grasp task. Accordingly, the entire population of cells showing task effects showed higher activation while the monkey was preparing the execution of a reach-to-grasp action (see Fig.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The monkey subjects were accustomed to sitting in a sphinx position in a plastic monkey chair, directly facing a liquid crystal display (LCD) screen (60 Hz frame rate), which was positioned at 57 cm from the monkeys‘ eyes 28 , 29 . During initial training, they were required to maintain fixation within a 2° × 2° window centered on a red fixation target (size: 0.18° × 0.18°) in the middle of the screen.…”
Section: Methodsmentioning
confidence: 99%
“…These convey the outflow of parietofrontal operations to subcortical centers and to the spinal cord. The analysis of the functional properties of cells in the many reach-related parietal and frontal areas and the study of their connections indicate that fast reaching and its online control are primarily encoded by a DRS (Caminiti et al, 2017), which also incorporate a grasping-related component (Filippini et al, 2017;Breveglieri et al, 2018;Nelissen et al, 2018), probably subserving an early coordination of reaching and grasping. This view on the DRS is also supported by the effects of reversible inactivation in monkeys, which mimics the defective online control of eye and arm movement (Battaglia-Mayer et al, 2013) typical of patients with parietal lesions resulting in optic ataxia (Balint, 1909;Pisella et al, 2000;Gréa et al, 2002;Buiatti et al, 2013).…”
Section: The Dorsal Reaching System (Drs)mentioning
confidence: 99%